EMERGING USE OF NONCONVENTIONAL TECHNOLOGIES DURING THE GLOBAL PANDEMIC (Nonconventional Technologies Review, 2022)
At the begining of the pandemic outbreak, medical supplies and medical devices were runing out in many countries resulting in great life loss. Major fields of science teamed up to help fighting this cause, engineers, health care personel, creators and inventors around the world tried to give aid in such a problematic field. Panic buying and rising demands disrupted the flow of the and the gobal supply chain in many countries resulting the need of an innovative, quick and easy solutions to be applied. Nonconvetional technologies are a well seen presence on the global market and with their help, on a global scale, many lives were saved and also huge steps towards evolution were done.
Keywords: Nonconvetional; Pandemic; COVID-19; PPE; Global scale